2013
DOI: 10.1123/jsm.27.4.288
|View full text |Cite
|
Sign up to set email alerts
|

Sport Sponsorship: The Relationship Between Team Loyalty, Sponsorship Awareness, Attitude Toward the Sponsor, and Purchase Intentions

Abstract: Sponsorship studies have generally been focused on attitudinal measures of fan loyalty to understand the reactions to abstract sponsors. This study examines the relationships between both attitudinal and behavioral loyalty with sponsorship awareness, attitude toward two actual sponsors, and purchase intentions. Data were collected among fans of a professional soccer team, and the results of a structural equation model provide evidence that attitudinal loyalty impacts the attitude toward both sponsors and purch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
252
1
22

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(304 citation statements)
references
References 59 publications
29
252
1
22
Order By: Relevance
“…However, the researchers targeted only CFC supporter clubs, which, per this study's invariance results, are homogenous groups that would not cast doubt on the validity of the research findings. Moreover, this study's sport fans displayed strong awareness, fit, attitude, and purchase intentions levels toward the sponsor across every analyzed country, which is in concordance with other sport sponsorship studies that have examined highly identified sport fans (e.g., Alexandris et al, 2012;Biscaia et al, 2013;Gwinner & Bennett, 2008). Fifth, the current study considered only five variables, and other variables may help to further explain sponsorship effectiveness.…”
Section: Limitations and Future Researchsupporting
confidence: 52%
See 3 more Smart Citations
“…However, the researchers targeted only CFC supporter clubs, which, per this study's invariance results, are homogenous groups that would not cast doubt on the validity of the research findings. Moreover, this study's sport fans displayed strong awareness, fit, attitude, and purchase intentions levels toward the sponsor across every analyzed country, which is in concordance with other sport sponsorship studies that have examined highly identified sport fans (e.g., Alexandris et al, 2012;Biscaia et al, 2013;Gwinner & Bennett, 2008). Fifth, the current study considered only five variables, and other variables may help to further explain sponsorship effectiveness.…”
Section: Limitations and Future Researchsupporting
confidence: 52%
“…In fact, attitude toward the sponsor was found to be the major predictor of purchase intentions for all analyzed countries, confirming the results of previous research on the link between attitude and intentions (cf. Biscaia et al, 2013). Thus, there are unique circumstances related to sport that international corporations should be aware of when they attempt to build more effective international sponsorship-linked marketing initiatives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of commitment has long been recognised as a key ingredient of any successful relationship (Morgan and Hunt 1994), whether it is commitment to personal relationships, such as marriage (Kelmer, Rhoades, Stanley and Markman 2013), or towards sports teams (Biscaia, Correia, Rosado, Ross and Maroco 2013), or towards non-profit organisations (Vecina, Chacón, Marzana and Marta 2013), to mention but a few.…”
Section: Student Commitmentmentioning
confidence: 99%